2019
DOI: 10.1186/s13018-019-1480-7
|View full text |Cite
|
Sign up to set email alerts
|

Total cross-sectional area of the femoral neck nutrient foramina measured to assess arterial vascular beds in the femoral head

Abstract: BackgroundA detailed understanding of the blood supply to the femoral head is required to plan the surgery in the femoral neck and head area. However, information about the blood vessel networks in the femoral head is inadequate.MethodsThe surface of the femoral neck of 100 dry cadaveric adult femur specimens was scanned using a 3D scanner. The scanning distance was 200 mm, precision 0.01 mm, and measuring point 0.04 mm. The images were acquired at a resolution of 1,310,000 pixels. Digital imaging data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Nevertheless, this approach does not apply to the nutrient foramina since the precision of CT is not sufficient for it. Three-dimensional scanning of the nutrient foramina has higher accuracy and allows the storage of information on the surface of the bone, which can be repeatedly studied; thus, reducing the demand for bone specimens ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, this approach does not apply to the nutrient foramina since the precision of CT is not sufficient for it. Three-dimensional scanning of the nutrient foramina has higher accuracy and allows the storage of information on the surface of the bone, which can be repeatedly studied; thus, reducing the demand for bone specimens ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, current CT scanners used in clinical practice do not meet the criteria for CT reconstruction to observe nutrient foramina ( 8 ). Currently, a 3D scanner can be applied to precisely measure the cross-sectional area of the nutrient foramina in the femoral neck of dry adult femur specimens ( 15 ). In our study, the 3-D model images obtained from a 3D scanner allowed for precise observation of the spatial locations of the nutrient foramina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study collected femoral head specimens comprising intact normal femoral heads and necrotic femoral heads. The dry bone specimens of the femoral head were used as the normal femoral head group, which were obtained from our published study [ 18 ]. The specimens of femoral head necrosis were obtained from two tertiary teaching hospitals, including Shanghai Sixth People’s Hospital affiliated to Shanghai Jiao Tong University School of Medicine and Tongji Hospital Affiliated to Tongji University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…The vascular supply condition of the femoral neck is determined by the nutrient foramina and is mandatory for the safe execution of surgery around the hip junction [ 13 15 ]. Previous observational studies on the nutrient foramina in the human femoral head showed that the size and number of nutrient foramina in the fovea capitis femoris of the human femoral head vary greatly among patients and different regions [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%